Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2478/v10289-012-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Honey Produced in the Homesha District of Western Ethiopia

Abstract: S u m m a r yThis study was conducted to characterize honey produced in the Homesha district in Western Ethiopia. The effects of location and hive type on the quality of honey produced in the area were assessed. A total of 20 honey samples were collected from four locations in the district. The overall mean (±SD) contents of reducing sugars, sucrose, pH, moisture, ash, hydroxymethylfurfural, acidity and water-insoluble solids of the honey samples analyzed were 65 ± 3.02%, 6.1 ± 3.4%, 4.02 ± 0.26, 16.4 ± 1.07%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In Ethiopia, the maximum acceptable amount of water-insoluble matter in honey is 0.1% (QSAE, 2005). The water-insoluble solids content observed in the present study is in line with the values of 0.01-0.46 g/100g reported by Gobessa et al (2012) for honey produced in the Homesha district of western Ethiopian. Alemu et al (2013) reported a higher waterinsoluble solids content of 0.53-0.70 g/100g for honey collected from Sekota district in northern Ethiopia.…”
Section: Physicochemical Properties Of the Honeysupporting
confidence: 92%
See 1 more Smart Citation
“…In Ethiopia, the maximum acceptable amount of water-insoluble matter in honey is 0.1% (QSAE, 2005). The water-insoluble solids content observed in the present study is in line with the values of 0.01-0.46 g/100g reported by Gobessa et al (2012) for honey produced in the Homesha district of western Ethiopian. Alemu et al (2013) reported a higher waterinsoluble solids content of 0.53-0.70 g/100g for honey collected from Sekota district in northern Ethiopia.…”
Section: Physicochemical Properties Of the Honeysupporting
confidence: 92%
“…Rane and Doke (2012) reported that reducing sugar content of honey samples from western Maharashtra/India ranged from 42.8% to 60.6%. Similarly, Gobessa et al (2012) reported reducing sugar contents ranging from 62 to 71% with a mean value of 65% for honey produced in the Homesha district of western Ethiopia. Muli et al (2007) reported reducing sugars content of 57.03-61.50% for Kenyan honey.…”
Section: Physicochemical Properties Of the Honeymentioning
confidence: 97%
“…Ethanol is further oxidized to acetic acid thus resulting in a sour taste [32]. The different moisture content of honey depends on harvesting season, the degree of maturity that honey reached in the hive, type of hive used, environmental temperature and moisture content of original plant [33,34]. Moisture content of honey can naturally be as low as 13% or as high as 23% depending on the source of the honey, climatic conditions and other factors [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, finding suitable chemical markers indicating the specific quality of honey linked to origin has been the focus of many studies in the last decade. This includes the studies dealing with the volatile compounds (Cuevas-Glory et al, 2007), phenolic content (Pyrzynska et al, 2009), physico chemical parameters (Gobessa et al, 2012), in honey of different floral and geographic origins.…”
Section: Introductionmentioning
confidence: 99%